A little history of religion - Holloway, Richard, 1933- (New Haven : Yale University Press, 2016)
In an era of hardening religious attitudes and explosive religious violence, this book offers a welcome antidote. Richard Holloway retells the entire history of religion from the dawn of religious belief to the twenty-first century with deepest respect and a keen commitment to accuracy. Writing for those with faith and those without, and especially for young readers, he encourages curiosity and tolerance, accentuates nuance and mystery, and calmly restores a sense of the value of faith. Ranging far beyond the major world religions of Judaism, Islam, Christianity, Buddhism, and Hinduism, Holloway also examines where religious belief comes from, the search for meaning throughout history, today's fascinations with Scientology and creationism, religiously motivated violence, hostilities between religious people and secularists, and more. Holloway proves an empathic yet discerning guide to the enduring significance of faith and its power from ancient times to our own.--INSIDE FLAP.
Is anybody there? -- The doors -- The wheel -- One into many -- Prince to Buddha -- Do no harm -- The wanderer -- In the bulrushes -- The ten commandments -- Prophets -- The end -- Heretic -- The last battle -- Worldly religion -- The way to go -- Stirring up the mud -- Religion gets personal -- The convert -- The messiah -- Jesus comes to Rome -- The church takes charge -- The last prophet -- Submission -- Struggle -- Hell -- Vicar of Christ -- Protest -- The big split -- Nanak's reformation -- The middle way -- Beheading the beast -- Friends -- Made in America -- Born in the USA -- The great disappointment -- Mystics and movie stars -- Opening doors -- Angry religion -- Holy wars -- The end of religion?
Print version record.
Master record variable field(s) change: 050
Keywords: Religions; Religion -- History; RELIGION -- Comparative Religion; RELIGION -- Essays; RELIGION -- Reference; Electronic books; History